Impact of nanoscale zerovalent iron on volatile fatty acid production from food waste: key enzymes and microbial community. Issue 10 (17th July 2019) - Jin, Yong; Gao, Ming; Li, Hongai; Lin, Yujia; Wang, Qunhui; Tu, Maobing; Ma, Hongzhi
Abstract: BACKGROUND: The proper dosage of nanoscale zerovalent iron (NZVI) for volatile fatty acid (VFA) production was optimized and different kinds of organic acids and key enzymes during the process were analyzed to test the effect of NZVI on VFA fermentation from food waste. RESULTS: Batch assays showed that proper NZVI dosage can promote VFA production, reaching the maximum accumulation of 22 250 mg COD L −1 at 10 g L −1 dosage, which is 1.92 times higher than that of the control group. Acetic acid accounted for the highest proportion (72%) of VFAs, and lactic acid was the main by‐product of organic acids. The addition of NZVI provided a reducing power for the lactic acid fermentation in the system, which promoted the conversion of pyruvic acid to lactic acid. Moreover, the addition of NZVI not only greatly promoted the activity of ferredoxin oxidoreductase (0.35 IU g −1 ) and acetyl‐CoA (1.47 IU g −1 ) but also caused changes in the microbial community structure in the fermentation system. After adding NZVI, besides Lactobacillus, Olsenella (12.69%) was another dominant bacterium which can rapidly convert the produced lactic acid into short‐chain fatty acids (SCFAs), thereby affecting acid production. CONCLUSION: These key enzymes resulted in the accumulation of VFAs. The fermentative bacteria responsible for SCFA production were also highly enriched in fermentation reactors with NZVI, which was in accordance with the accumulation of SCFAs. © 2019 Society of Chemical Industry